Providing a Contaminant and Mitigation Analysis Tool for Enhanced Decision Making and Knowledge Acquisition. (September 2015) - Danczyk, Jennifer; Jacobs, Paula; Farry, Mike
Environmental awareness has become an important consideration within military training facilities. Facility managers are tasked with scheduling mitigation events to prevent the transport of toxic waste accumulated from training exercises to neighboring bodies of water, which harms surrounding ecosystems and communities. Currently there isn't an easy way to perform this task due to facility managers lacking knowledge in environmental concepts and contaminant properties. To assist facility managers, we conducted domain analysis for the design of a decision support tool that is equipped with models, visualizations, and information on toxic properties and transport phenomenon of contaminants. We created an intuitive representation displaying appropriate timing to perform mitigation events. Feedback on the validity of our prototype was received by subject matter experts familiar with current processes used for contaminant analysis and mitigation scheduling. With further development, this tool will improve the efficiency of military training facilities scheduling efforts while optimizing monetary savings.